Features of inner courtyard spaces in traditional Chinese dwellings and their application in modern regional architectural design - Zhang Yimeng; Korotich Andrey V. (Архитектон, 2024)
The article examines the formal characteristics and morphotypes of courtyard spaces in traditional Chinese dwellings, including compositional solutions for groups of courtyard spaces. Continuity of such spaces in modern regional architectural creativity is considered. Based on an analysis of several modern Chinese regional architectural projects, the ways of integrating the courtyard spaces of traditional Chinese buildings into a modern architectural context are discussed. Examples are provided, showing the reconstruction and metaphorical reinterpretation of both individual spaces and combined structures of group spaces of courtyards in the context of integration of modern architectural creativity with traditional national and regional architecture.